Six-month periodic fasting does not affect somatosensory nerve function in type 2 diabetes patients - Kender, Zoltan; von Rauchhaupt, Ekaterina; Schwarz, Daniel; Tsilingiris, Dimitrios; Schimpfle, Lukas; Bartl, Hannelore; Longo, Valter D.; Bendszus, Martin; Kopf, Stefan; Herzig, Stephan; Heiland, Sabine; Szendroedi, Julia; et al. (Frontiers in Endocrinology, 2023)
Background and aim: Current strategies for preventing diabetic sensorimotor polyneuropathy (DSPN) are limited mainly to glucose control but rapid decrease of glycemia can lead to acute onset or worsening of DSPN. The aim of this study was to examine the effects of periodic fasting on somatosensory nerve function in patients with type 2 diabetes (T2D). Study design and methods: Somatosensory nerve function was assessed in thirty-one patients with T2D (HbA1c 7.8±1.3% [61.4±14.3 mmol/mol]) before and after a six-month fasting-mimicking diet (FMD; n=14) or a control Mediterranean diet (M-diet; n=17). Neuropathy disability score (NDS), neuropathy symptoms score (NSS), nerve conduction velocity and quantitative sensory testing (QST) were analyzed. 6 participants of the M-Diet group and 7 of the FMD group underwent diffusion-weighted high-resolution magnetic resonance neurography (MRN) of the right leg before and after the diet intervention. Results: Clinical neuropathy scores did not differ between study groups at baseline (64 % in the M-Diet group and 47 % in the FMD group had DSPN) and no change was found after intervention. The differences in sensory NCV and sensory nerve action potential (SNAP) of sural nerve were comparable between study groups. Motor NCV of tibial nerve decreased by 12 % in the M-Diet group (P=0.04), but did not change in the FMD group (P=0.39). Compound motor action potential (CMAP) of tibial nerve did not change in M-Diet group (P=0.8) and increased in the FMD group by 18 % (P=0.02). Motor NCV and CMAP of peroneal nerve remained unchanged in both groups. In QST M-diet-group showed a decrease by 45 % in heat pain threshold (P=0.02), FMD group showed no change (P=0.50). Changes in thermal detection, mechanical detection and mechanical pain did not differ between groups. MRN analysis showed stable fascicular nerve lesions irrespective of the degree of structural pathology. Fractional anisotropy and T2-time did not change in both study groups, while a correlation with the clinical degree of DSPN could be confirmed for both. Conclusions: Our study shows that six-month periodic fasting was safe in preserving nerve function and had no detrimental effects on somatosensory nerve function in T2D patients.